Unlocking the therapeutic potential of P2X7 receptor: a comprehensive review of its role in neurodegenerative disorders - Liu, Xiaoming; Li, Yiwen; Huang, Liting; Kuang, Yingyan; Wu, Xiaoxiong; Ma, Xiangqiong; Zhao, Beibei; Lan, Jiao (Frontiers in Pharmacology, 2024)
The P2X7 receptor (P2X7R), an ATP-gated ion channel, has emerged as a crucial player in neuroinflammation and a promising therapeutic target for neurodegenerative disorders. This review explores the current understanding of P2X7R's structure, activation, and physiological roles, focusing on its expression and function in microglial cells. The article examines the receptor's involvement in calcium signaling, microglial activation, and polarization, as well as its role in the pathogenesis of Alzheimer's disease, Parkinson's disease, multiple sclerosis, and amyotrophic lateral sclerosis. The review highlights the complex nature of P2X7R signaling, discussing its potential neuroprotective and neurotoxic effects depending on the disease stage and context. It also addresses the development of P2X7R antagonists and their progress in clinical trials, identifying key research gaps and future perspectives for P2X7R-targeted therapy development. By providing a comprehensive overview of the current state of knowledge and future directions, this review serves as a valuable resource for researchers and clinicians interested in exploring the therapeutic potential of targeting P2X7R for the treatment of neurodegenerative disorders.